Implications of RERA and GST on Construction Sector in Maharashtra - Pawar, Priyanka S.; Patil, Dhananjay S. (SOTVI, 2023)
The real estate industry serves as a catch-all for addressing a nation's housing and infrastructural needs. It significantly improves five sub-divisions, including dwellings, infrastructure, shopping, lodging, and business. As a common practice across the nation, the real estate industry lacked professionalism, uniformity, and consumer protection. A new era in the Indian real estate industry has been assured with the introduction of the Real Estate Regulator Bill (RERA), which was approved by the Indian Parliament in March 2016. This measure, which was approved by the Indian parliament, creates a more open, accountable, and reliable framework for the construction industry, with a primary focus on the real estate market for selling and buying homes. The newly implemented Goods and Services Tax (GST) also introduced tremendous changes in the Real Estate Market. This made Real Estate Market slow in its Initial Stages which left Builders and Contractors to stay away from the Business for a particular period of time, to confront themselves with the new laws and the new taxation system